Experimental study of the mechanical behavior of dam sediment renforced by geotextiles and geogrids - Meksi, Ali; Sadoun, Mohamed; Youzera, Hadj; Benmahdi, Khaled; Bouguenina, Otbi (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Geosynthetic materials have been successfully used for soil reinforcement to improve bearing capacity. In this article, geotextiles are used as tension material for the reinforcement of a mixture based on dredged sediment from the Cheurfas dam (Mascara) and quarry sand. Methods: Immediate bearing index tests were carried out in the laboratory to study the mixing behaviour, and the three-point bending flexural test was carried out on prismatic specimens to study the traction capacity of the mixture. Mixture samples are selected and tested without reinforcement. Then, by placing one, two and three layers of geotextile at a certain depth of the sample, the effects of a number of layers and type of geotextile and geogrid on increasing the bearing capacity of the mixture are discussed. Results: The results of these tests show that the bearing capacity of the samples reinforced by geotextile and geogrid is increased compared to that of the unreinforced samples. Based on the results obtained from Proctor-IPI, their values do not permit the movement of construction machinery during the construction of pavement layers.The Immediate Bearing Index values are found sufficient for pavement layers. Geotextile introduction increases traction strength and improves stress distribution on soil samples, with the effect being significant for woven geotextile blends. Conclusion: All things considered, the results point to the possibility of using reinforced local soils as an affordable and practical option for building pavements. To guarantee long-term performance and optimise building methods, more research is advised.